تحليل أدوات البحث العلمي لطلبة قسم تعليم اللغة العربية بجامعة الأستاذ كياهي الحاج سيف الدين زهري الإسلامية الحكومية ببورووكرتو - Ruswatie, Ade (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah; Vol 1 No 1 (2023): مجموعة البحوث - الملتقى العلمي العالمي للدراسات العربية, 2024)
Research instruments play an important role in writing scientific research, because they are what lead to obtaining the data needed in the scientific research process. If the researcher chooses the appropriate scientific research instruments, he will obtain data that suits the research topic and can answer the research questions. The students of the Department of Arabic Language Education at Professor K.H. Saifuddin  Zuhri State Islamic University are still confused when selecting these research instruments, and these chosen research tools were not suitable for their research for the research topic. Thus, this research aimed to analyze the scientific research tools of students in the Arabic Language Education Department . This research is an analytical library research because the researcher analyzed the research instruments used by researchers in the Arabic Language Teaching Department. The data sources for this research are documentation from Sarjana’s research. After the researcher conducted the research, the result of the research was that the students in the Arabic Language Teaching Department who had completed their studies in the Sarjana stage still made the mistake when assigning the research instruments corresponding to their research, because there is evidence that they assigned the research tools and did not obtain the data that answers the research questions and data. appropriate to the research topic. They made a mistake in specifying the type of research, and this supports the error in specifying the data collecting method and the research instruments used. تدور أدوات البحث دورا مهما في كتابة البحث العلمي، لأنها التي تسبب إلى نيل البيانات المحتاجة في عملية البحث العلمي. إذا اختار الباحث أدوات البحث العلمي المناسبة سينال البيانات التي تناسب موضوع البحث وتستطيع أن تجيب أسئلة البحث. فطلبة قسم تعليم اللغة العربية بجامعة الأستاذ كياهي الحاج سيف الدين زهري الإسلامية الحكومية مازالوا في الحيران عند تعيين هذه أدوات البحث ولم تكن هذه أدوات البحث المختارة مناسبة ببحثهم. وبهذا، هدف هذا البحث إلى تحليل أدوات البحث العلمي لطلبة قسم تعليم اللغة العربية. هذا البحث من البحث المكتبي التحليلي لأن الباحثة قامت بتحليل أدوات البحث المستخدمة من قبل الرسالة العلمية للطلبة في قسم تعليم اللغة العربية، أما مصادر البيانات لهذا البحث هو التوثيق من رسالة سرجانا. وبعد أن قامت الباحثة بالبحث حصلت على نتيجة البحث أن الطلبة في قسم تعليم اللغة العربية الذين قد أتموا دراستهم في مرحلة سرجانا مازالوا في الخطأ عند تعيين أدوات البحث المطابقة ببحثهم، وذلك لوجود الدليل أنهم عينوا أدوات البحث ولم يحصلوا على البيانات التي تجيب أسئلة البحث والبيانات المناسبة لموضوع البحث. وهم أخطؤوا في تعيين نوع البحث وهذا يدعم إلى الخطأ في تعيين أسلوب جمع البيانات وأدوات البحث المستخدمة.